Agricultural Modernisation in China: The Second Leap - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2008)
Three decades after Deng Xiaoping initiated agricultural reform and market liberalisation, China’s countryside is experiencing a second evolution as it transits from traditional to modern agriculture. According to Singapore Management University social science researchers Forrest Zhang and John Donaldson, agribusinesses of various forms, sizes and origins are playing a key role in this process, known as the “second leap”.